Dust-free starburst galaxies at redshifts z > 10. Issue 1 (21st February 2023) - Nath, Biman B; Vasiliev, Evgenii O; Drozdov, Sergey A; Shchekinov, Yuri A
ABSTRACT: One of the most distant galaxies GN-z11 was formed when the Universe was ≤400 Myr old, and it displays a burst-like star formation rate ∼25 M⊙ yr −1 with a metallicity Z ∼ 0.2 ± 0.1 Z⊙ . It resembles z  = 2–3 galaxies (at 'cosmic noon') except for the fact that the measured reddening E ( B − V ) = 0.01 ± 0.01 indicates the presence of little or no dust. This marked absence of dust hints towards violent dynamical events that destroy or evacuate dust along with gas out of the galaxy on a relatively short time-scale and make it transparent. We apply a 3D numerical model to infer possible physical characteristics of these events. We demonstrate that the energetics of the observed star formation rate is sufficient to tear apart the dusty veil on time-scales of 20–25 Myr. This can explain the apparent lack of evolution of ultraviolet luminosity function of galaxies between z ≥ 10 and z ∼ 7, by compensating for the lower galaxy masses at higher redshift by the absence of dust. We show, however, that this is a temporary phenomenon and soon after the last of the supernovae explosions have taken place, the expanding shell shrinks and obscures the galaxy on time-scales of ≈5–8 Myr.